2022
DOI: 10.7554/elife.77643
|View full text |Cite
|
Sign up to set email alerts
|

A dopamine-gated learning circuit underpins reproductive state-dependent odor preference in Drosophila females

Abstract: Motherhood induces a drastic, sometimes long-lasting, change in internal state and behavior in many female animals. How a change in reproductive state or the discrete event of mating modulates specific female behaviors is still incompletely understood. Using calcium imaging of the whole brain of Drosophila females, we find that mating does not induce a global change in brain activity. Instead, mating modulates the pheromone response of dopaminergic neurons innervating the fly's learning and memory center, the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 110 publications
0
5
0
Order By: Relevance
“… 12 , 19 21 , 40 42 , 59 61 Interestingly, the majority of reports define a role for MBns in innate behavioral responses to food-related odors. 12 , 18 20 , 40 42 Our results, using more general, non-food odors, puts the hypothesis that MBn regulates innate behavior on more solid ground. Importantly, we found that MB dDA1 is required for state-dependent behavior to general odors ( Figure 5C ).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“… 12 , 19 21 , 40 42 , 59 61 Interestingly, the majority of reports define a role for MBns in innate behavioral responses to food-related odors. 12 , 18 20 , 40 42 Our results, using more general, non-food odors, puts the hypothesis that MBn regulates innate behavior on more solid ground. Importantly, we found that MB dDA1 is required for state-dependent behavior to general odors ( Figure 5C ).…”
Section: Discussionmentioning
confidence: 68%
“… 17 However, recent discoveries have revealed that the Drosophila mushroom body (MB) is required for innate olfactory behavior as well as its historically defined role in learning. 12 , 18 20 The current hypothesis states that both behaviors are driven by cholinergic connections between MB neurons (MBns) and downstream MB-output neurons (MBONs) 21 and that innervating dopaminergic neurons (DANs) modulate this connection in response to learning and internal state. It is unknown how dopaminergic input to the MB controls these two discrete behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that MBON-α′3 forms a suppressed short-lived memory trace following aversive olfactory conditioning, whose activity is required for the 15-min memory [ 56 ]. In addition, MBON-β′1 activity is critical for polyamine odor preference and mating behaviors in female flies [ 57 ]. Our results showed the physiological roles of MBON-α′3 and MBON-β′1, which are responsive to hot stimuli and regulate HAB execution in Drosophila ( Fig 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation for our findings is that, after their initial encounter with the food, the ants are less hungry, and thus food becomes less of a motivation to learn in subsequent visits. Such state-dependent learning has been demonstrated in insects in both foraging ( Pompilio et al, 2006 ) and mating ( Boehm et al, 2022 ) contexts, and has been implicated in the driving of preference in ants ( Czaczkes et al, 2018 ). While ants continue to make many tens of foraging visits if allowed, demonstrating a consistent and high motivation ( Oberhauser et al, 2020a ), the first encounter with a food source after 4 days of food deprivation is likely to be especially salient.…”
Section: Discussionmentioning
confidence: 99%